2018
DOI: 10.1371/journal.pone.0205346
|View full text |Cite
|
Sign up to set email alerts
|

Parameters that remain consistent independent of pausing before gait-initiation during normal rise-to-walk behaviour delineated by sit-to-walk and sit-to-stand-and-walk

Abstract: BackgroundRising-to-walk is an everyday transitional movement task rarely employed in gait rehabilitation. Sit-to-walk (STW) and sit-to-stand-and-walk (STSW), where a pause separates sit-to-stand and gait-initiation (GI) represent extremes of rising-to-walk behaviour. Delayed GI can indicate pathological impairment but is also observed in healthy individuals. We hypothesise that healthy subjects express consistent biomechanical parameters, among others that differ, during successful rising-to-walk task perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
(56 reference statements)
5
9
2
Order By: Relevance
“…Significantly greater hesitation was observed during STS than during STW in this group of people early after stroke. This finding is similar to previous findings that hesitation is greater during STS than STW in healthy younger adults (25) despite the variation in the description and calculation of hesitation between studies. As the events of hesitation (maximum forward velocity and maximum upward acceleration) both occur around the end of Phase 1 of movement, the flexion momentum, these data indicate that hesitation is likely contributing factor to the longer Phase 1 of movement seen in STS compared to STW.…”
Section: The Differences Between Movement Fluidity and Duration Of Phases Between Sts And Stwsupporting
confidence: 91%
See 3 more Smart Citations
“…Significantly greater hesitation was observed during STS than during STW in this group of people early after stroke. This finding is similar to previous findings that hesitation is greater during STS than STW in healthy younger adults (25) despite the variation in the description and calculation of hesitation between studies. As the events of hesitation (maximum forward velocity and maximum upward acceleration) both occur around the end of Phase 1 of movement, the flexion momentum, these data indicate that hesitation is likely contributing factor to the longer Phase 1 of movement seen in STS compared to STW.…”
Section: The Differences Between Movement Fluidity and Duration Of Phases Between Sts And Stwsupporting
confidence: 91%
“…Hesitation of both STS and STW was measured as the percentage of normalized time between the maximum forward velocity and the maximum upward acceleration of the clavicle marker, where a low value indicates a fluid movement without hesitation. In contrast to previous publications (24,25), here hesitation does not measure the depression in horizontal momentum. It was considered important to change the calculation for hesitation to provide an equitable measure between the tasks of STS and STW:…”
Section: Hesitationcontrasting
confidence: 82%
See 2 more Smart Citations
“…One study analyzed the characteristics of this transition with and without a pause before gait initiation. 14) This study found that pausing before initiating gait requires less positional stability even in healthy individuals. Another study found that increases in angular velocity and linear accelerations during STW may predispose healthy, young individuals for balance loss.…”
Section: ⅰ Introductionmentioning
confidence: 74%